Dose enhancement effects of gold nanoparticles specifically targeting RNA in breast cancer cells [dataset] - Hildenbrand, Georg Lars; Metzler, Philipp; Pilarczyk, Götz; Bobu, Vladimir; Hosser, Hiltraud; Fleckenstein, Jens; Krufczik, Matthias; Bestvater, Felix; Wenz, Frederik; Hausmann, Michael (Universität, 2017)
Localization microscopy has shown to be capable of systematic investigations on the arrangement and counting of cellular uptake of gold nanoparticles (GNP) with nanometer resolution. In this article, we show that the application of specially modified RNA targeting gold nanoparticles (“SmartFlares”) can result in ring like shaped GNP arrangements around the cell nucleus. Transmission electron microscopy revealed GNP accumulation in vicinity to the intracellular membrane structures including them of the endoplasmatic reticulum. A quantification of the radio therapeutic dose enhancement as a proof of principle was conducted with γH2AX foci analysis: The application of both - SmartFlares and unmodified GNPs - lead to a significant dose enhancement with a factor of up to 1.2 times the dose deposition compared to non-treated breast cancer cells. This enhancement effect was even more pronounced for SmartFlares. Furthermore, it was shown that a magnetic field of 1 Tesla simultaneously applied during irradiation has no detectable influence on neither the structure nor the dose enhancement dealt by gold nanoparticles.
Gesehen am 05.12.2017
Keywords: Forschungsdaten; Datenbank